دور مشاهدة أفلام العنف في تشكيل شخصية المراهق - بلعيد، خديجة, بكاكرة، شهرة (جامعة الوادي university of Eloued, 2021)
الملخص: تهدف دراستنا هاته إلى معرفة تأثير مشاهدة أفلام العنف في تشكيل شخصية المراهق في مرحلة المراهقة المتأخرة (18إلى 25 سنة). والتي خصصناها لطلبة السنة الأول جامعي. تمت صياغة السؤال الرئيسي على النحو التالي: إلى أي مدى تؤثر فلام العنف على تشكيل شخصية المراهق؟ أما التساؤلات الفرعية شكلناها كالتالي: - ما مدى إقبال المراهقين على أفلام العنف؟ - ما هي دوافع مشاهدة أفلام العنف؟ - هل تؤثر أفلام العنف على المراهقين بشكل واحد؟ تعتبر هذه الدراسة من الدراسات الوصفية، والتي تم الاعتماد فيها على المنهج الوصفي التحليلي. ولجمع البيانات من الميدان تم من خلال أداة الملاحظة البسيطة والاستبيان، والذي احتوى على17 سؤال،واعتمدنا كذلك على العينة القصدية قوامها 150 مفردة من طلاب السنة أولى من العلوم الإنسانية بجامعة الشهيد حمه لخضر ولاية الوادي، بطريقة عشوائية. وتم التوصل إلى النتائج التالية: هناك قِبال ضعيف على مشاهدة أفلام العنف نظرا لسمات العامة لعينة الدراسة كالفئة العمرية ومستوى المعيشي. تباينت دوافع تعرض المراهقين لأفلام العنف بين الحاجة للتسلية وملء وقت الفراغ وكذلك تعلم منها للدفاع عن نفس. تؤثر أفلام العنف على المراهقين بشكلاً واحداً في كافة النواحي السلوكية، كتعاطف مع الضعيف، زيادة نبضات القلب، أحلام مزعجة وكوابيس في النوم وغيرها من النواحي السلوكية. كما أكسبته تصرفات لطيفة كالتسامح مع الغير و غيرها . Résumé :إنجليزية This study aims to find out the effect of watching violent films on shaping the personality of the adolescent in the late adolescence stage (18 to 25 years). Which we allocate for first-year university students. The main question was formulated as follows: To what extent does violence film affect the formation of the adolescent's personality? The sub-questions are as follows: - What is the demand of teenagers for violent films? What are the motives for watching violent films? Do violent films affect teenagers in the same way? This study is considered one of the descriptive studies, which relied on the descriptive analytical method. To collect data from the field, it was done through a simple observation tool and a questionnaire, which contained 17 questions, and we also relied on an intentional sample of 150 first-year students of human sciences at the University of Martyr Hama Lakhdar, El Wadi state, in a random manner. The following results were obtained: There is a weak appetite for watching violent films due to the general characteristics of the study sample, such as the age group and standard of living. The motives of adolescents' exposure to violent films varied between the need for entertainment and to fill free time, as well as learning from them to defend oneself. Violent films affect adolescents in one way in all behavioral aspects, such as sympathy for the weak, increased heart rate, disturbing dreams and nightmares in sleep and other behavioral aspects. It also earned him nice behavior such as tolerance with others and others.
دراسة مسحية على عينة من طلبة سنة أولى علوم إنسانية لجامعة الشهيد حمة لخضر بالوادي
مذكرة ماستر إعلام تخصص سمعي بصري
Keywords: المراهقة، الشخصية، أفلام العنف; Films sur l'adolescence, la personnalité et la violence; Adolescence, Personality, Violence Films